2022
DOI: 10.3390/agriculture12030429
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antagonistic Effect of Pseudomonas Rhizobacteria on Fusarium Wilt of Chickpea

Abstract: This study aimed to isolate rhizobacteria belonging to the genus Pseudomonas with plant-growth-promoting properties that can be used in the control of chickpea wilt disease caused by Fusarium oxysporum f. sp. ciceris (Foc). The production of antifungal compounds by the isolated rhizobacteria was assessed against two Foc isolates, coded Foc-S1 and Foc-S2. Strains E1FP13, E1FP4, and E1PP7 were the most effective against Foc-S1, with percentages of 52.77%, 48.37%, and 47.97%, respectively, while E1PP6, E1FP13, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…PGPR is important for sustainable crop production and achieving food security (Ajilogba et al, 2022a). PGPR for crop yield and quality increase as well as disease/pathogen control has been extensively studied in many crops such as soybean (Silva et al, 2019;Riviezzi et al, 2021), rice (Raja et al, 2017;Xu et al, 2019), maize (Ke et al, 2019;Olanrewaju and Babalola, 2019a;Liu et al, 2020), wheat (Kumar et al, 2018;Ma et al, 2021), chickpea (Laranjeira et al, 2021;Khalifa et al, 2022), and cowpea (Kanthaiah and Velu, 2019;Kumar et al, 2021).…”
Section: Plant-growth Promoting Rhizobacteria For Bgn Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…PGPR is important for sustainable crop production and achieving food security (Ajilogba et al, 2022a). PGPR for crop yield and quality increase as well as disease/pathogen control has been extensively studied in many crops such as soybean (Silva et al, 2019;Riviezzi et al, 2021), rice (Raja et al, 2017;Xu et al, 2019), maize (Ke et al, 2019;Olanrewaju and Babalola, 2019a;Liu et al, 2020), wheat (Kumar et al, 2018;Ma et al, 2021), chickpea (Laranjeira et al, 2021;Khalifa et al, 2022), and cowpea (Kanthaiah and Velu, 2019;Kumar et al, 2021).…”
Section: Plant-growth Promoting Rhizobacteria For Bgn Productionmentioning
confidence: 99%
“…Many studies have reported their use in controlling various plant pathogens. For example, by producing the metabolite, wuyiencin, Streptomyces albulus CK-15 controls powdery mildew of cucumber (Yang et al, 2021), while Bacillus (Cui et al, 2019(Cui et al, , 2020Castaldi et 2021), Rhizobium (Wong et al, 2021;Kawaguchi and Noutoshi, 2022), and Pseudomonas (Omoboye et al, 2019;Khalifa et al, 2022) species have been reported in the biocontrol of some plant species. PGPR acts via direct and indirect mechanisms to control plant pathogens.…”
Section: Biological Control and Disease Resistance Associated With Pl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas spp . demonstrated a significant reduction in disease incidence and an increase in chickpea growth [ 5 , 6 ]. Meanwhile, Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, biocontrol agents have emerged as a potential alternative to chemical fungicides to prevent and control various diseases due to their green and pollution-free characteristics (Niem et al, 2020;Huang et al, 2021;Yuan et al, 2022). The antagonistic microorganisms that can inhibit the postharvest diseases of fruits and vegetables include species of Candida, Bacillus, Pseudomonas, yeast, and Wickerhamomyces (Spadaro and Droby, 2016;Kang et al, 2019;Khalifa et al, 2022). Among them, Bacillus has been widely isolated and utilized as an effective biocontrol agent.…”
Section: Introductionmentioning
confidence: 99%